Deposição e caracterização de filmes finos TaA1N por magnetron sputtering reativo - Oliveira, Givanilson Brito de (2017)
Ta-Al-N thin films were prepared using reactive magnetron sputtering, in order to verify the influence of the aluminum content on the crystalline structure, hardness and oxidation resistance. The samples were characterized by Grazing Incidence X-ray Diffraction (GIXRD), Energy Dispersive Spectroscopy (EDS), Rutherford Backscattering Spectrometry (RBS), nanohardness analysis and oxidation tests at 500°C, 600°C and 700°C. First, it was necessary to define deposition parameters of stoichiometric TaN with face centered cubic structure. From this, TaAlN thin films were prepared and present at concentration of 2, 5, 7, 14, 24 and 41 at.%. The crystal phase for the TaAlN films was only present with addition up to 5 at.%, increasing the Al concentration the coatings will tend to be amorphous. From the SEM analysis was possible to observe the surface of the film after oxidation, all thin films showed irregularities, however the amount of such failures was lower in samples with low aluminum content. Moreover, the addition of aluminum does not result in significant gains for oxidation resistance. The highest hardness value obtained was 29 GPa for the sample containing 14 at.%.